Addition of abiraterone, docetaxel, bisphosphonate, celecoxib or combinations to androgen-deprivation therapy (ADT) for metastatic hormone-sensitive prostate cancer (mHSPC): a network meta-analysis. Issue 4 (November 2018) - Tan, Pui; Aguiar, Pedro; Haaland, Benjamin; Lopes, Gilberto
Abstract Background Patients with metastatic prostate cancer have poor prognosis. In this study, we compared the addition of abiraterone, docetaxel, bisphosphonate, celecoxib or combinations to standard ADT vs. ADT alone for patients with mHSPC in terms of overall survival (OS), failure-free survival (FFS), and adverse events. Methods We searched PubMed and performed a network meta-analysis to generate probabilistic inferences and provide efficacy rankings in terms of posterior hazard ratios with 95% credible intervals (CrI), surface under the cumulative ranking curve (SUCRA), probability better than competing treatments, and probability best. Results Seven trials were included (LATITUTE, STAMPEDE, CHAARTED, GETUG-AFU15, ZAPCA, CALGB 90202, and MRC PR05). Compared to ADT alone, evidence suggests abiraterone + ADT (OS HR: 0.60; 95% CrI: 0.50–0.71, FFS HR: 0.31; 95% CrI: 0.25–0.38) could be superior in terms of OS and FFS compared to docetaxel + ADT (OS 0.74; 95% CrI: 0.63–0.86, FFS 0.62; 95% CrI: 0.53–0.74), bisphosphonate + ADT (OS: 0.87; 95% CrI: 0.75–1.00, FFS 0.87; 95% CrI: 0.75–1.00), celecoxib + ADT (OS: 0.91; 95% CrI: 0.71–1.17, FFS: 0.86; 95% CrI: 0.68–1.08), or triple combinations. Abiraterone + ADT suggests improved survival with 97% certainty for a 19% reduction in risk of death compared to docetaxel + ADT (HR: 0.81; 95% CrI: 0.66–1.00). Discussion Addition of abiraterone to standard ADT may possibly outperform the addition of docetaxel, bisphosphonates, celecoxib, or combinations to standard ADT in terms of OS and FFS.